Investigating the crystallization process of a ternary alloy system with a new nano-cluster analysis by using molecular dynamics method - Celik, F. A.; Kazanc, S.; Ozgen, S.; Yildiz, A. K. (Elsevier Science Bv, 2011)
In this study, the crystallization process of Cu-%26,8Al-%2,5Ni ternary alloy during annealing has been investigated using molecular dynamics simulation based on the variations oflocal order and atomic rearrangements. The interactions between atoms were modeled by Sutton-Chen type of embedded atom method (SCEAM) based on many body interaction. The structural development and phase transformations are analyzed from the variations of the radial distribution function (RDF). The bonded pairs determined from Honeycutt-Andersen (HA) method for the binary alloy systems are defined as bonded triples for the ternary alloy system unlike the application in mono-atomic and binary alloy systems known in literature. (C) 2011 Published by Elsevier Masson SAS.
Keywords: Nano-clusters; Crystallization; Cu-Al-Ni; Molecular dynamics